(untitled) (Journal of Bhuwanishankar, 2024)
This study explores the effect of dehumanizing deeds of female genital mutilation, and discriminatory and orthodoxical sexual perception toward women boosted by religion and perpetuated particularly by woman in Ali’s autobiography, Infidel. It also reveals how patriarchal society frowns on a woman’s plea for sexual liberation as a real freedom. In Infidel, a mediocre Somali girl transforms herself into a freedom fighter realizes her true essence and also becomes a member of the parliament of the Netherlands. Ali’s memoir clearly illustrates the subordination of females in Muslim society and how their bodily autonomy is confined by religious norms. The poignant story of female genital mutilation, the issue of their virginity, decency in the way they dress, restriction in the movement and the situation of their insecurity and vulnerability in broad daylight are some of the most prominent issues she has highlighted throughout her writing. These are the impeding factors that curb women’s freedom. The book explicitly presents the unshakeable faith of Ali in herself and her self-determination and daring personality. This book chronicles her inner evolution from a girl hailing from the most marginalized part of the world, Somalia, to the world’s eminent advocate against Muslim fundamentalism. This study has adopted a qualitative research method of textual analysis with the theoretical lens of feminism and relies primarily on the concepts from the book to establish an argument by the secondary source of information gathered from journals, books and reports.